Environmental assessment of the mineral extraction and non-renewable energy due to dense graded hot mix and warm mix asphalts processes (2023)
This paper describes the assessment of the use of resources such as mineral extraction and non-renewable energy of a dense graded hot mix asphalt production in a facility located in Colombia, considering four different scenarios for comparison purposes; the reference scenario is the conventional hot mix asphalt process, and the other three scenarios assess the impact of adding three different additives that help lowering the mixing temperatures. These additives allow for lower temperatures during the mixing and laying processes, and this technology is known as warm mix asphalt process. The inventory analysis of the life cycle was done by gathering and calculating information related to the inputs and outputs of the process, in order to identify the hypothesis and limits of the study. Data files of the company were consulted, from January 2011 to June 2012. Based on the inputs and outputs, mass and energy balances were verified, in order to establish the goals and scope for the assessment. The units used for the mass balances were kg/month, and the units for energy balance were MJ/month. Based on this information, the process was quantitatively described. Each units of the process was associated to relevant data, while some stages of the process were excluded of this analysis. Specialized software for Life Cycle Analysis (LCA) and several databases were used to analyze the process stages that involve most of the time and effort of the dense graded hot mix asphalt. Some limitations related to the data gathering were defined; the data excluded from this study were associated to the exploitation and transport of aggregates from the source to the plant, the crude oil refining for producing asphalt binder, and its transportation from the refinery to the mixing plant. Copyright © 2015, AIDIC ServiziS.r.l.